Solution:
![(x+1)(2x-4)(\frac{1}{x}+1)=(x+1)(2x-4)(1-\frac{5}{2x}-4)\\(x+1)(2x-4)(\frac{1}{x}+1)-(x+1)(2x-4)(1-\frac{5}{2x}-4) = 0\\(x+1)(2x-4)(\frac{1}{x}+1-(1-\frac{5}{2x}-4))=0\\(x+1)(2x-4)(\frac{1}{x}+1-(-3\frac{5}{2x}))=0\\(x+1)(2x-4)(\frac{1}{x}+1+3+\frac{5}{2x})=0\\(x+1)(2x-4)(\frac{1}{x}+4+\frac{5}{2x})=0\\(x+1)(2x-4)(\frac{5x^{2}+8x+2}{2x} )=0\\](https://tex.z-dn.net/?f=%28x%2B1%29%282x-4%29%28%5Cfrac%7B1%7D%7Bx%7D%2B1%29%3D%28x%2B1%29%282x-4%29%281-%5Cfrac%7B5%7D%7B2x%7D-4%29%5C%5C%28x%2B1%29%282x-4%29%28%5Cfrac%7B1%7D%7Bx%7D%2B1%29-%28x%2B1%29%282x-4%29%281-%5Cfrac%7B5%7D%7B2x%7D-4%29%20%3D%200%5C%5C%28x%2B1%29%282x-4%29%28%5Cfrac%7B1%7D%7Bx%7D%2B1-%281-%5Cfrac%7B5%7D%7B2x%7D-4%29%29%3D0%5C%5C%28x%2B1%29%282x-4%29%28%5Cfrac%7B1%7D%7Bx%7D%2B1-%28-3%5Cfrac%7B5%7D%7B2x%7D%29%29%3D0%5C%5C%28x%2B1%29%282x-4%29%28%5Cfrac%7B1%7D%7Bx%7D%2B1%2B3%2B%5Cfrac%7B5%7D%7B2x%7D%29%3D0%5C%5C%28x%2B1%29%282x-4%29%28%5Cfrac%7B1%7D%7Bx%7D%2B4%2B%5Cfrac%7B5%7D%7B2x%7D%29%3D0%5C%5C%28x%2B1%29%282x-4%29%28%5Cfrac%7B5x%5E%7B2%7D%2B8x%2B2%7D%7B2x%7D%20%29%3D0%5C%5C)
![x+1=0\\x=-1\\\\2x-4=0\\x=2\\\\\frac{5x^{2}+8x+2}{2x}=0\\x=\frac{-4+\sqrt[]{6}}{5}\\x=\frac{-4-\sqrt[]{6}}{5}](https://tex.z-dn.net/?f=x%2B1%3D0%5C%5Cx%3D-1%5C%5C%5C%5C2x-4%3D0%5C%5Cx%3D2%5C%5C%5C%5C%5Cfrac%7B5x%5E%7B2%7D%2B8x%2B2%7D%7B2x%7D%3D0%5C%5Cx%3D%5Cfrac%7B-4%2B%5Csqrt%5B%5D%7B6%7D%7D%7B5%7D%5C%5Cx%3D%5Cfrac%7B-4-%5Csqrt%5B%5D%7B6%7D%7D%7B5%7D)
Answer:
![x=-1\\x=2\\x=\frac{-4+\sqrt[]{6}}{5}\\x=\frac{-4-\sqrt[]{6}}{5}](https://tex.z-dn.net/?f=x%3D-1%5C%5Cx%3D2%5C%5Cx%3D%5Cfrac%7B-4%2B%5Csqrt%5B%5D%7B6%7D%7D%7B5%7D%5C%5Cx%3D%5Cfrac%7B-4-%5Csqrt%5B%5D%7B6%7D%7D%7B5%7D)
<em>Hope this was helpful.</em>
The length of a table, the width of a classroom, and the length of a car can be easily measured without using trigonometry (could probably use a meter stick or measuring tape) because we can easily reach both ends
the width of a wide river is a little different, it may not be practical to measure the distance across directly.
Answer:
15 years and 8 months
Step-by-step explanation:
I used the formula for compound interest as shown below and solved for the unknown, time.
Since our interest is compounded annually (So once a year) our m value is 1.
Mmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmm